2016
DOI: 10.2527/jas.2016-0726
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uncoupling protein 1 in bovine muscle cells1

Abstract: Uncoupling protein 1 (Ucp1) is predominantly expressed in brown/beige adipocytes in mammals. Although myogenic cells have been suggested to commit to a brown adipocyte lineage through the induction of Prdm16 expression, Prdm16 is also expressed in skeletal muscle. Thus, we examined expression of Ucp1 in bovine myogenic cells. Considering that Ucp1 is a principle molecule that induces energy expenditure in brown/beige adipocytes, expression of Ucp1 is not preferable in beef cattle because of potential decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Immunohistochemical studies showed positive staining for UCP1 at the peripheral region of muscle fibres but not in adipocytes resident in the skeletal muscle. Expression levels of Ucp1 were higher in myosatellite cells cultured under the myogenic condition than in those under the adipogenic condition 3 . These results suggest that bovine myogenic cells express Ucp1 .…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Immunohistochemical studies showed positive staining for UCP1 at the peripheral region of muscle fibres but not in adipocytes resident in the skeletal muscle. Expression levels of Ucp1 were higher in myosatellite cells cultured under the myogenic condition than in those under the adipogenic condition 3 . These results suggest that bovine myogenic cells express Ucp1 .…”
Section: Introductionmentioning
confidence: 67%
“…We previously demonstrated that bovine Ucp1 expression is increased with progression of myogenesis, with levels significantly higher on day 12 than on day 6, after induction of myogenesis in myosatellite cells 3 . Endogenous TGF‐β/activin pathway negatively regulates murine myogenesis 19,29 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations